2021
DOI: 10.21521/mw.6564
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy-associated glycoprotein concentrations during early gestation in pregnant Awassi sheep

Abstract: This study was aimed at determining the serum pregnancy-associated glycoprotein (PAG) profile of pregnant Awassi sheep during early gestation. A total of 122 Awassi ewes were used, which were in days 28-56 (28, 30, 32, 36, 42, 49, and 56) of gestation. Blood samples were taken via jugular venepuncture. Out of these animals, 104 ewes that had delivered (singleton lambs, n = 60; twin lambs, n = 44), according to lambing records, were selected for the assessment of serum PAG levels. The serum PAG level was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Previous studies have reported that serum PAGs and PSPB levels determined with the RIA and sheep ELISA methods were higher in multiple pregnant ewes, compared to singleton pregnant ewes (Akkuş & Yaprakcı, 2022 ; El Amiri et al., 2014 , 2015 ; Ranilla et al., 1997 ). However, the differences observed in the serum PAGs levels of singleton and multiple pregnant ewes measured with bovine PAG‐ELISA pregnancy tests do not change the results of pregnancy diagnosis (Akköse et al., 2021 ; Alkan et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported that serum PAGs and PSPB levels determined with the RIA and sheep ELISA methods were higher in multiple pregnant ewes, compared to singleton pregnant ewes (Akkuş & Yaprakcı, 2022 ; El Amiri et al., 2014 , 2015 ; Ranilla et al., 1997 ). However, the differences observed in the serum PAGs levels of singleton and multiple pregnant ewes measured with bovine PAG‐ELISA pregnancy tests do not change the results of pregnancy diagnosis (Akköse et al., 2021 ; Alkan et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the breed, plasma PAGs levels have been reported to alter during pregnancy (Milisits‐Németh et al., 2018 ; Redden & Passavant, 2013 ; Ranilla et al., 1994 ). In previous research conducted in Türkiye, the early pregnancy serum PAGs levels of ewes of the Konya Merino (Kaplan et al., 2018 ; Uçar et al., 2018 ) and Awassi (Akköse et al., 2021 ) breeds, both of which are commonly raised in the country, have been monitored. This study was aimed at the comparative assessment of the early pregnancy serum PAGs profiles of Karya ewes, characterized by high milk production and fertility, and Konya Merino ewes, bred for meat and wool production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the gestation period, the mononucleate and binucleate cells of the ruminant trophectoderm generate pregnancy-associated glycoproteins (PAGs), which originate from the placenta ( Sousa et al, 2006 ). Around day 18 or day 20 following breading, PAGs can be observed in the serum of pregnant ewes ( Barbato et al, 2009 ) and are a reliable indication of pregnancy among ruminants, such as goats ( Singh et al, 2021 ), sheep ( Akköse et al, 2021 ), and cattle ( Silva et al, 2007 ). Progesterone (P 4 ) is a crucial hormone for determining pregnancy in ewes ( Schneider & Hallford, 1996 ).…”
Section: Introductionmentioning
confidence: 99%